Discovering search behaviour in black garden ant trajectories - Perrine Bonavita; Marius Albino; Jacques Gautrais; Vincent Fourcassié; Maud Combe; Loic Lacour; Simon Eibner; Christian Jost (PLoS ONE, 2026)
Exploratory behaviour plays an important role in many animals, in particular for social insects who have to feed and protect a whole colony. In a laboratory study, Khuong et al (2013) studied how workers of the black garden ant Lasius niger move around in an unknown environment. They assumed that, in a homogeneous arena with no visual cues, ants had no information about their position in space. Based on this hypothesis, they modelled ant movement in a Boltzmann Walker framework which describes an ant’s random walk as a series of straight segments separated by reorientation events. They found that, on a plain horizontal surface, an ant’s heading does not influence its speed, segment length and reorientation decision, thus leading to diffusive trajectories. However, published experiments indicate that L. niger ants are not completely devoid of directional information, even in standard laboratory setups with no obvious visual landmarks. Moreover, many ant species are known to develop specific search strategies when they want to find a particular place in space, a situation that may apply to the data Khuong el al analysed. We re-analysed their data on a plain horizontal surface, this time taking into account the ant’s heading in relation to its starting point in the arena. We discovered that the distributions of segment lengths and reorientation angles are modulated by the ant’s orientation in relation to its starting point. By simulating these biased trajectories, we show that this modulation leads to an area-restricted search behaviour. We also show that this modulation considerably accelerates the return times of ants to their starting point when they find themselves far from it. We conclude that not taking into account the animal’s cognitive abilities in data analysis may lead to incomplete or biased conclusions. The discovered search behaviour in L. niger can play a significant role in the colony’s exploration and foraging ecology.